AMBERGRIS SEBAGAI KOMODITAS EKONOMI DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Fakhrurozi, Moh; Warsiyah, Warsiyah; Sari, Mutiara; Tyas Nurulia , Eki; Saputri, Noorikha Pandayahesti Saputeri (Universitas Islam Negeri Raden Intan Lampung, 2025)
Ambergris, a rare substance produced from the digestive system of sperm whales (Physeter macrocephalus), has high economic value and is widely used in the luxury perfume industry. However, its controversial existence from an ecological, ethical, and religious point of view raises questions in the context of Islamic economics. This article analyzes the ambergris trade through an Islamic approach to business ethics, highlighting the principles of justice, openness, prohibition of exploitation, and the potential elements of gharar and maysir. This study uses a literature study method based on normative and qualitative approaches, with primary sources of fiqh muamalah and Islamic business ethics theory. The findings show that the trade in ambergris can be categorized as conditionally halal, but it must meet Islamic moral and ecological principles so as not to cause damage and uncertainty that is contrary to maqashid al-shari'ah. Keywords: ambergris, Islamic economics, business ethics, justice, gharar, maysir.